2016
DOI: 10.4103/1596-3519.172555
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of hepatitis B virus serological markers among pregnant Nigerian women

Abstract: Background:Chronic hepatitis B infection is a global problem; however, Asia and sub-Saharan Africa are most affected by it. Hepatitis B status of pregnant women is essential for the effective management of the disease and prevention of mother to child transmission.Materials and Methods:The study was conducted at the antenatal care unit of four hospitals within Kaduna Metropolis, Nigeria, between August and December 2011. After obtaining ethical clearance, blood samples were collected from 800 consenting pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 26 publications
1
7
3
Order By: Relevance
“…Even though age has been identified to be a major determinant of HBV incidence and its, however, from this study, HBsAg detection was not significantly associated with age (P = 0.836) even though the highest prevalence was among the patient aged between 51 and 60 years. The age-specific prevalence in this study is in contrast with the findings of (Olokoba et al, 2011;Aba and Aminu, 2016) who reported that the highest prevalence was recorded in the age range 21 and 35 years. Also, our results are similar to the findings of (Manjula et al, 2018) that mentioned age factor in individuals was >40 years.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Even though age has been identified to be a major determinant of HBV incidence and its, however, from this study, HBsAg detection was not significantly associated with age (P = 0.836) even though the highest prevalence was among the patient aged between 51 and 60 years. The age-specific prevalence in this study is in contrast with the findings of (Olokoba et al, 2011;Aba and Aminu, 2016) who reported that the highest prevalence was recorded in the age range 21 and 35 years. Also, our results are similar to the findings of (Manjula et al, 2018) that mentioned age factor in individuals was >40 years.…”
Section: Resultscontrasting
confidence: 99%
“…The 6.5% recorded for HBsAg in this study is higher than the 5.7% recorded in Ekiti (Opaleye et al, 2014) and lower that the 9.7% in Niger Delta (Ejele et al, 2004), 11.9% in Ibadan (Otegbayo et al, 2008), 15% in North-Eastern Nigeria (Olokoba et al, 2008) and 16.7% in Jos (Idoko et al, 2009). The prevalence recorded in this study is higher than 2.3% in Kaduna (Aba and Aminu, 2016) and lower than a 5.8% recorded in Owerri (Nwolisa et al, 2013). The geographical variation, differences in cultural practices, sexual behaviour and practices as well as differences in the test methods employed in detection can play an important role in the disease epidemiology and surveillance.…”
Section: Resultscontrasting
confidence: 54%
“…The global prevalence of hepatitis B is among the highest in parts of Africa, containing an estimated 50 million chronic carriers of HBV [ 13 , 14 ]. Previous studies have shown HBsAg positive rates above 10% in African countries such as Burkina Faso, the Central African Republic, and Nigeria [ 15 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…of 26, 548. Seventeen of the 20 studies (85%) were facility-based cross-sectional studies [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57], two studies were retrospective chart reviews [58,59], and one was a community-based cross-sectional study [60]. Half of the studies were conducted in the Northern region (North Central = 5; North East = 2; and North West = 3) [41-44, 46, 52, 54, 56, 57, 60] and the remaining 50% were conducted in the Southern region (South East = 1 and South West = 9) [45, 47-50, 53, 55, 58, 59].…”
Section: Plos Onementioning
confidence: 99%